Energy and nutrient content of weight-loss diets published in high-circulation newspapers - GÜNEŞ, FATMA ESRA; AKTAÇ, ŞULE (ASOC ESPANOLA DIETISTAS NUTRICIONISTAS, 2021)
Introduction: The press is one of the most effective methods to provide the public with health education and to increase knowledge levels related to health in society. Nutritional advice and weight loss diets are also frequently featured in newspapers. However, diets in newspaper limit food groups and/or nutrients to achieve faster results. This study aimed to assess diet lists published in newspapers in terms of energy and nutrient contents and to compare levels with requirements. Material and Methods: From 1th February 2018 to 31th January 2019, nutritional and diet news included in 10 newspapers with high circulation in Turkey were investigated and diets published in these newspapers were investigated. The energy, macro, and micronutrient contents were compared with the Turkey Nutrition Guide recommendations. Results: It appeared diet lists met 55.5% of energy requirements for women and 44.5% of energy requirements for men. Carbohydrate and protein contents of diets were below recommendations, while fat contents were identified to be above-recommended levels. Dietary fiber was determined to meet 81.2% of recommendations. For micronutrients, calcium and iron contents were below recommended levels. Conclusions: It appears weight-loss diets in newspapers are insufficient in terms of energy and some nutrients. Though these diets, which are easily accessible by a large portion of society, without expert control they may cause nutrient deficiencies in the long term.
Keywords: Diet; Periodical; Nutrients; Weight Loss; Newspaper; LOW-CARBOHYDRATE DIETS; HEALTH; WOMEN; TERM